TakoTsubo secondary to acute kidney disease - Angelica Cersosimo; Gianmarco Arabia; Enrico Vizzardi (Monaldi Archives for Chest Disease, 2023)
We report the case of a 62-year-old man who was admitted to the Cardiac Department for TakoTsubo and ACC by torsades de point, secondary to acute kidney disease. We decide to discharge with a portable defibrillator. One month after cardiac magnetic resonance showed a complete recovery of left ventricular function.